Risk Analysis of Berry Harvesting in a Blueberry Plantation - Michniewicz, Wiesław; Pogorzelski, Grzegorz; Lesiów, Tomasz (Analiza ryzyka dotyczącego pozyskania jagód na plantacji borówki, 2022)
The purpose of the study was to conduct a risk analysis of the operation of a highbush blueberry plantation based on the FMEA method. The research was based on the information acquired from two private blueberry plantations differing in location (Sokolniki, Dybów) and acreage size (0.45 ha and 4 ha). It was pointed out that the greatest threat to both plantations, and thus to the quality of the product, turned out to be ensuring proper fertilization and protection from diseases and pests (risk index: 126). In addition, in the case of the first plantation, the location of the plantation (147), cutting and shaping of bushes that have a significant impact on plant development (120) and protection from wild birds (112) were of great importance. Similarly, plantation location, cutting and bush formation (162), yields, commercial quality of the harvest, and plantation location (112) were diagnosed as high risks for the second plantation. The most critical risks to blueberry quality occur at the first link in the logistics chain, i.e. the agricultural producer.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2022, Nr 38, s. 111-123